Antimicrobial formulation and functionalization of photosensitizers for antimicrobial photodynamic therapy (aPDT) - Khurana, Bhavya (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2022)
To provide a long-lasting solution to infections affecting the current world scenario, antimicrobial photodynamic therapy (aPDT) offers a non-invasive means to destroy pathogenic microbes via formation of reactive oxygen species (ROS) on irradiation with an appropriate wavelength of light of a photosensitizing molecule, photosensitizer (PS). This ROS species promotes the damage of microbial targets such as nucleic acids (DNA or RNA), proteins, lipids, protein complexes, or by impeding the biofilm matrix. This manuscript work presents an inclusive study into synthetic and post-synthetic strategies made towards enhancing the efficiency of PSs for this therapy. More explicitly, it provides an insight to making a PS aPDT compatible by combining it with a drug delivery system or synthetically altering the molecular skeleton of the PS with functionalities which induces better potency towards the site of infection. The synthetic strategies, spectroscopic characterizations and photophysical characterization including the production of singlet oxygen species via DPBF degradation assays are discussed along this manuscript. Different strategies for making the PS ideal for use in aPDT have been done which includes making water-soluble biopolymeric hyaluronic acid (HA) conjugates with synthesized PSs based on chlorin and porphyrin macrocycles or by synthesizing BODIPY scaffolds with different meso-aryl groups and post functionalizing these derivatives with different functionalities enhancing their spectrum towards inactivation of bacterial cultures. Finally, these conjugates as well as BODIPY derivatives have been tested against bacteria, finding that some of these molecules were able to inhibit the growth of bacteria and their biofilms under light irradiation, demonstrating the efficiency of such strategies for a potential aPDT.
Formulation antimicrobienne et fonctionnalisation de photosensibilisateurs pour la th?rapie photodynamique antimicrobienne (aPDT)
APPROVED
Keywords: Keywords: Photosensitizers, Antimicrobial photodynamic therapy (aPDT), Hyaluronic acid, BODIPY, Singlet Oxygen, Diphenylbenzofuran (DPBF)